(3GdYjhf hGdMOGFb aj GdCNHGQ hGdMbGFbs ((3MSf Hf CHj GdaQL Hf GdMSjf GdcjGd GdaGQbi s)
(3ChdgG (B:s
(3NdGaI GdhdjO Hf YHO Gdedc SfI (B86(3g` s
(3BNQgG (B:s
(3Je GdLRA GdKGdK ef GdYjhf hGdMOGFb s
(3GdehLhO efg GdLRA GdKGdKs
(3jfJgi Edi NdGaI GdeYJUe HGddg SfI (B229(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B587 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B221 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs